THE TERM JIHAD IN ISLAMIC JURISPRUDENCE WITH REFERENCE TO MODERN INTERNATIONAL LAW: A CRITICAL EXAMINATION - Nehaluddin Ahmad; Mohd Wafiq bin Mohd Jafree (Journal of Malaysian and Comparative Law, 2025)
The term “jihad” carries with it several negative connotations, where the term can be linked with acts of violence, extremism, and terrorism. This article goes against such views and argues that jihad is defensive in nature. It is to be contended that jihad can be utilized as a cause for self-defence, not as a means to enable aggression. In addition, the role of jihad under Islamic law will be compared briefly within the context of modern international law. Moreover, this article will further clarify the term “jihad” by reviewing its meaning and common misconceptions. This article also highlights that the term jihad is misunderstood, it is essentially a tool of selfdefence and a last resort against oppressors and mandates that all other efforts must be tried before turning to violence. The claim that jihad is a holy war against non-Muslims is thus untrue from a philosophical and theoretical standpoint and does not reflect the fundamental principles of Islamic jurisprudence. Instead, this paper argues that jihad is a cause for self-defence rather than a cause of aggression.